Celebrating 95th Anniversary of Professor R.S. Belkin. A Brief Biographical Sketch - E. R. Rossinskaya (Теория и практика судебной экспертизы)
The article is dedicated to the 95th birthday anniversary of the eminent Soviet and Russian forensic researcher, Distinguished Scientist, Doctor of Law, Professor R.S. Belkin. It looks at the milestones of his creative career in the development of Russian criminalistics and forensic expertology. Included is a detailed overview of Prof. R.S. Belkin's most significant scientific works on the general theory of criminalistics, forensic techniques, forensic tactics, and the general theory of forensic science (forensic expertology).